Handling Agricultural Waste as Alternative Feed in Beef Cattle Business Groups in Baruga Village, Kendari City - Hajar; Harianti; Hasriati; Tao, Harudin; Sasmita, Farra; Latif, Wd Umrawati; Maulid S, Awal (Jurnal Pengabdian Masyarakat Bestari, 2024)
UNSULTRA Internal Community Service Activities (PKM-UNSULTRA) carried out by a team of lecturers from the Faculty of Agricultural Technology located in Baruga Village, Kendari City. Introducing how to make cattle feed using agricultural waste feed ingredients using appropriate processing methods in the beef cattle farming business group. Community service activities aim tutilize and apply feed from agricultural waste. Processing in the manufacture of feed from agricultural waste as an alternative feed to replace forage during the dry season. This is intended so that farmers can make their own feed and run their livestock business in a more focused manner. The results of the activity show that there has been an increase in knowledge and skills in better feed processing in the use of agricultural waste into feed for beef cattle as well as business management.